Implementasi High-Availability WordPress Deployment Berbasis Teknologi AWS - Martin Gunawan Manurung; Akhyar Lubis; Hafni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In the current digital era, the reliability and availability of websites have become critical factors in business operations. However, many organizations that use WordPress often face problems with the availability and access speed of their sites. This research focuses on the implementation of High Availability (HA) on WordPress using Amazon Web Services (AWS) as a solution to these problems. The research approach involves the use of a prototype method, which allows for concept testing and rapid iteration in a controlled environment. This process involves collecting data on server infrastructure and cloud computing, as well as configuring and testing relevant AWS services. The main goal is to develop a reliable and efficient WordPress infrastructure, focusing on the implementation of Elastic Load Balancing, Amazon RDS, storage buckets, and CDN distribution in the Lightsail environment. The research results show a significant improvement in the performance and reliability of WordPress sites. The HA implementation involves strategies such as using Elastic Load Balancing for efficient traffic distribution, data storage on Amazon RDS, and static media storage with storage buckets and content distribution. Performance evaluation confirms that the proposed solution improves the availability and access speed of WordPress sites.